Consumption culture in Europe insight into the beverage industry - Rodríguez Santos, María Carmen 1975-; Ganassali, Stéphane; Casarin, Francesco; Laaksonen, Pirjo 1943-; Kaufmann, Hans Rüdiger 1958- (Research essentials, 2013)
"This book offers the most relevant theories about culture and European market segmentation as well as providing updated data for the evaluation and analyses of the European consumption patterns in the beverage market"...Provided by publisher